TOWARDS THE CONCEPT OF GLOBULAR PEARLITE - A. G. Anisovich; M. K. Stepankova; A. A. Andrushevich (Литьë и металлургия, 2017)
Explanatory imprecisions of concept of globular pearlite and ferrite-carbide-mixture are considered. The need of concept binding of globular pearlite to specific grain with 0.8% carbon content is explained with the assistance of exemplary data obtained at the present metallographic equipment. The question of educational material presentation concerning the process of teaching of discipline «Materials and construction materials technology» is discussed in relation to the educational process of technical universities, in particular, the Belarusian State Agrarian Technical University.